2022
DOI: 10.1021/acscatal.2c04308
|View full text |Cite
|
Sign up to set email alerts
|

From Stoichiometric to Catalytic E–H Functionalization by Non-Metallocene Zirconium Complexes─Recent Advances and Mechanistic Insights

Abstract: The chemistry of group 4 elements has historically been dominated by the use of metallocene complexes in stoichiometric transformations. While this area continues to be widely explored, the development of non-cyclopentadienyl-based ligands has substantially contributed to the increase in applicability of group 4 metals in catalysis during the last 15 years. In addition to their application in polymerization catalysis, zirconium complexes supported by nitrogen-based anionic ligands have been useful as catalysts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 194 publications
(296 reference statements)
0
4
0
Order By: Relevance
“…Rigorous characterization of zirconium complexes supported by L1 have previously afforded insightful crystalline samples of isolated catalytic intermediates. 59 Thus, stoichiometric reactions were pursued to isolate the putative allyl zirconium intermediates ( Scheme 4 ). Known alkyl amido complex 6-Si 48 was dissolved in C 6 D 6 and treated with 1 equiv.…”
Section: Resultsmentioning
confidence: 99%
“…Rigorous characterization of zirconium complexes supported by L1 have previously afforded insightful crystalline samples of isolated catalytic intermediates. 59 Thus, stoichiometric reactions were pursued to isolate the putative allyl zirconium intermediates ( Scheme 4 ). Known alkyl amido complex 6-Si 48 was dissolved in C 6 D 6 and treated with 1 equiv.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work from our group has shown that bis­(ureate) proligand L1 facilitates the isolation of intermediates in catalysis. This approach has been used to obtain mechanistic insights of related C–C and C–N bond-forming reactions catalyzed by bis­(ureate)-supported zirconium complexes . Accordingly, to understand the source of the contrasting reactivity between N -benzylaniline and N -(trimethylsilyl)­benzylamine in alkyne hydroaminoalkylation, we undertook stoichiometric reactivity studies using these two different amine substrates.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This approach has been used to obtain mechanistic insights of related C−C and C−N bond-forming reactions catalyzed by bis(ureate)-supported zirconium complexes. 35 Accordingly, to understand the source of the contrasting reactivity between N-benzylaniline and N-(trimethylsilyl)benzylamine in alkyne hydroaminoalkylation, we undertook stoichiometric reactivity studies using these two different amine substrates. Alkylamido complexes such as 3 are reliable precursors for accessing bis(ureate) supported zirconaaziridine intermediates in situ (4, Scheme 3).…”
Section: Substrate Effects On Alkyne Hydroaminoalkylationmentioning
confidence: 99%
“…The thusly formed nitrogen-containing compounds including N -heterocycles offer diverse applications not only in material sciences, but also in natural product synthesis and pharmaceutical chemistry. One synthetic concept in the mostly applied preparation of such molecules is the hydroamination reaction [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%